2015
DOI: 10.1111/plb.12348
|View full text |Cite
|
Sign up to set email alerts
|

How to define nativeness in vagile organisms: lessons from the cosmopolitan mossBryum argenteumon the island of Tenerife (Canary Islands)

Abstract: The distinction between native and introduced biotas presents unique challenges that culminate in organisms with high long-distance dispersal capacities in a rapidly changing world. Bryophytes, in particular, exhibit large distribution ranges, and some species can truly be qualified as cosmopolitan. Cosmopolitan species, however, typically occur in disturbed environments, raising the question of their nativeness throughout their range. Here, we employ genetic data to address the question of the origin of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Furthermore, recent phylogeographic evidence suggests that formerly endemic Macaronesian species have colonized several times the western Atlantic fringe of Europe since the last glacial maximum 28 . Within the endemic element of the Macaronesian bryophyte flora, the strong genetic structure observed at small scales 39 40 41 and significant shifts in the expression of mating systems and associated dispersal life-history traits 2 point, however, to dispersal limitations. These observations raise substantial concerns on the ability of Macaronesian bryophyte species to migrate to macroclimatically suitable areas on the continent as a response to the dramatic decrease of their suitable areas on the islands during the next decades.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent phylogeographic evidence suggests that formerly endemic Macaronesian species have colonized several times the western Atlantic fringe of Europe since the last glacial maximum 28 . Within the endemic element of the Macaronesian bryophyte flora, the strong genetic structure observed at small scales 39 40 41 and significant shifts in the expression of mating systems and associated dispersal life-history traits 2 point, however, to dispersal limitations. These observations raise substantial concerns on the ability of Macaronesian bryophyte species to migrate to macroclimatically suitable areas on the continent as a response to the dramatic decrease of their suitable areas on the islands during the next decades.…”
Section: Discussionmentioning
confidence: 99%
“…, though see Collins and Cruickshank for a critique) or methods that utilize molecular clocks coupled with population genetics to determine whether a species arrived in a location prior to human colonization (Pisa et al. ). While our approach cannot provide species identifications for specimens absent from the reference library, it can be used to prioritize which specimens are examined by trained taxonomists.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, DNA approaches fail to identify potential quarantine species when previously sequenced individuals of that species are missing from the reference library. While previous research has shown that the utility of DNA sequences to improve biosecurity monitoring can further be increased through the integration of multiple forms of analysis (Collins et al 2012), other approaches that might improve the identification of these "known-unknown" and "unknown-unknown" specimens that are absent from reference libraries includes the use of multi-species multi-locus coalescent (Dowton et al 2014, though see Collins and Cruickshank 2014 for a critique) or methods that utilize molecular clocks coupled with population genetics to determine whether a species arrived in a location prior to human colonization (Pisa et al 2015). While our approach cannot provide species identifications for specimens absent from the reference library, it can be used to prioritize which specimens are examined by trained taxonomists.…”
Section: Applicability For Biosecurity and Quarantine Monitoringmentioning
confidence: 99%
“…the limited number of population genetic studies in island bryophytes prevents the emergence of robust conclusions on the effects of founder events in insular bryophytes (Q26). No signature of a bottleneck was found in populations of Bryum argenteum in tenerife, possibly because of recurrent immigrations events (Pisa et al 2015). If this pattern is indeed recurrent, it could prevent endemic speciation due to gene flow intensity (Vanderpoorten et al 2008(Vanderpoorten et al , 2011 or niche pre-emption (Silvertown et al, 2005), assuming that competition could play a sufficient role to shape bryophyte communities.…”
Section: Dispersal and Colonizationmentioning
confidence: 96%
“…despite that variation of genetic diversity and similarity along elevation gradients (Pisa et al 2015, Sim-Sim et al 2015 suggests that island bryophytes may diversify as a response to environmental variation, they are characterized by non-radiating speciation modes within archipelagic regions (Patiño et al 2014a) and thus do not seem to be prone to ecological diversification (Q23-24). Pócs (2006) discussed potential radiations in Caribbean Pilotrichum P. Beauv.…”
Section: Speciation and Diversificationmentioning
confidence: 99%